Ambler Class A Extended-Spectrum Beta-Lactamase-Producing Escherichia coli and Klebsiella spp. in Canadian Hospitals - Mulvey, Michael R. (American Society for Microbiology, 2004)
This report describes a study carried out to gain baseline information on the molecular characteristics of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and Klebsiella spp. in Canada. A total of 29,323 E. coli and 5,156 Klebsiella sp. isolates were screened at 12 participating sites. Of these, 505 clinically significant, nonrepeat isolates displaying reduced susceptibility to the NCCLS-recommended beta-lactams were submitted to a central laboratory over a 1-year period ending on 30 September 2000. A total of 116 isolates were confirmed to be ESBL producers. PCR and sequence analysis revealed the presence of TEM-11 (n = 1), TEM-12 (n = 1), TEM-29 (n = 1), TEM-52 (n = 4), CTX-M-13 (n = 1), CTX-M-14 (n = 15), CTX-M-15 (n = 11), SHV-2 (n = 2), SHV-2a (n = 12), SHV-5 (n = 6), SHV-12 (n = 45), and SHV-30 (n = 2). Five novel beta-lactamases were identified and designated TEM-115 (n = 2), TEM-120 (n = 1), SHV-40 (n = 2), SHV-41 (n = 4), and SHV-42 (n = 1). In addition, no molecular mechanism was identified for five isolates displaying an ESBL phenotype. Macrorestriction analysis of all ESBL isolates was conducted, as was restriction fragment length polymorphism analysis of plasmids harboring ESBLs. Although a “clonal” distribution of isolates was observed at some individual sites, there was very little evidence suggesting intrahospital spread. In addition, examples of identical or closely related plasmids that were identified at geographically distinct sites across Canada are given. However, there was considerable diversity with respect to plasmid types observed.